Arduino LCD thermometer / Aizat Shawal and Mohamad Azrin Abu Yamin - Shawal, Aizat; Abu Yamin, Mohamad Azrin (2015)
A thermometer is an instrument for measuring and indicating temperature. It is often a sealed glass tube that contains a column of liquid, as mercury that expands and contracts or rises and falls with the temperature changes. The temperature being read where the top of the column coincides with a calibrated scale marked on the tube or its frame. Now in technology era, the digital thermometer was developed to replace the analog thermometer. The development of an analog thermometer is complicated. It is also have poor range accuracy and precision of measurement and takes a few minutes to measure the temperature. So from that problem statement our objectives are to improve the thermometer from analog to digital and display the temperature reading Ori. the LCD'. There are three main important components that used in this project. There are LCD, sensor, LEDs and Arduino circuit. The function of LCD is used to display the measured temperature. The sensor is used to sense the temperature and the Arduino circuit is used to control the overall circuit. The LEDs are used to indicate the temperature whether its. normal or not which is the green's LED will light up when temperature is normal while red's LED will light up when the temperature is hot. With that, we have successful doing our final year project and all objectives have been achieved.